Role of the Human Rights Ombudsman in Ensuring Good Administration in Slovenia - Kornelija Marzel (Central European Public Administration Review)
According to the Constitution of the Republic of Slovenia and the Human Rights Ombudsman Act, the Slovenian Ombudsman is established to protect human rights and fundamental freedoms in relation to public authorities. It is important that the Ombudsman not only complies with the provisions of the Constitution and international legal acts, but that when intervening, the Ombudsman may invoke the principles of fairness and good administration. The purpose of the article is to contribute to the understanding of good administration and related circumstances for the respect or violation of human rights. The article is based on the idea that by applying the principles of good administration, public authority undermines the public belief that bureaucracy is an end in itself and is in a dominant position. With these principles, public authority focuses on parties which realise their rights and enjoy their freedoms through the principles and postulates of a democratic society. Both theoretical and empirical research methods were used in the preparation of the article. The analysis of complaints to the Ombudsman aimed to verify the compliance of normative, theoretical bases with actual practice, and to establish the basis for evaluating the existing model of the Slovenian Ombudsman, all in the context of the study of good administration. The results together with theoretical findings facilitated the verification that in practice, public authorities most frequently violate the principles of good administration and that the Ombudsman may significantly contribute to good administration within their powers. The findings of this article are an original contribution to understanding ombudsmen and their role in different countries.